Correlations between the kinetics and the mechanisms of hot corrosion of pure nickel at 700 °C. (15th July 2019) - Grégoire, Benjamin; Montero, Xabier; Galetz, Mathias C.; Bonnet, Gilles; Pedraza, Fernando
Highlights: In synthetic air, pure nickel formed a duplex oxide scale with a steady-state oxidation rate. Addition of 0.5% SO2/SO3 to synthetic air considerably increased the kinetics of degradation of pure nickel. NiSO4 has been successfully identified at the scale/gas interface upon exposure in synthetic air + 0.5% SO2/SO3. Both Na2SO4 and thermal cycling increased the kinetics of hot corrosion of pure nickel. The maximum attack occurred when Type-II hot corrosion conditions were fulfilled. Abstract: This study investigates the kinetics of hot corrosion of pure nickel exposed to different testing conditions at 700 °C. Whereas nickel underwent pure oxidation when exposed to synthetic air only, the addition of 0.5% SO2 /SO3 induced oxidation-sulphidation and considerably increased the corrosion kinetics. In the presence of sodium sulphate (Na2 SO4 ), Ni-S liquid solutions systematically formed at the metal/scale interface. This was attributed to the shielding effect of Na2 SO4 implying negative pO2 and pSO3 gradients from the gas/salt interface towards the scale/salt interface. The influence of thermal cycling as well as the testing method (i.e. half-embedding and salt-recoating) was also elucidated.